2017
DOI: 10.1016/j.scriptamat.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intermetallic particles on the initiation and growth behavior of hydrogen micropores during high-temperature exposure in Al-Zn-Mg-Cu aluminum alloys

Abstract: The X-ray tomography technique is employed to observe the effects of intermetallic compound particles on the nucleation and growth of hydrogen micropores at high temperatures in Al-Zn-Mg-Cu aluminum alloys. Hydrogen micropores are heterogeneously nucleated on particles during exposure at 748 K. Growth and coalescence of the hydrogen micropores are observed with increasing exposure time.Interactions between hydrogen micropores and particles have a significant influence on the growth and coalescence of hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The work by Su et al [14] indicates that nucleated hydrogen micropores in particles show premature growth when under loading, revealing such research also that between 7 to 28% of fractures originate from hydrogen micropores. Often, in Al-Mg alloys, about half of hydrogen atoms are trapped in such micropores.…”
Section: Blister Formation Mechanism Through Oxide Filmmentioning
confidence: 92%
See 2 more Smart Citations
“…The work by Su et al [14] indicates that nucleated hydrogen micropores in particles show premature growth when under loading, revealing such research also that between 7 to 28% of fractures originate from hydrogen micropores. Often, in Al-Mg alloys, about half of hydrogen atoms are trapped in such micropores.…”
Section: Blister Formation Mechanism Through Oxide Filmmentioning
confidence: 92%
“…The analyzes of these authors show that a pure aluminum did not form micropores at heat treatment temperature of 550 °C in a time of 90 h. However, the hydrogen was trapped in its microstructure. Su et al [14] and Toda et al [49] identified that hydrogen gets stuck in vacancies, making it impossible to move vacancies. For a sample of Al-Zn-Mg alloy, Su et al [15] indicated distribution of hydrogen in favorable regions and its atomic concentration in regions, as shown in Figure 7.…”
Section: Blister Formation Mechanism Through Oxide Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…12) Hydrogen micro pores are initiated heterogeneously on the intermetallic particles during the homogenization process. 9,13) In contrast, vacancies due to extensive plastic deformation are stabilized and agglomerated into nano voids in the presence of hydrogen during the rolling process. 14) During the in-situ tensile tests, it can be seen that nano voids are initiated uniformly across the whole specimen with an increase in applied strain levels, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Su, et al have proposed that internal hydrogen tends to be accumulated in the equivalent strain concentration region during deformation. 13) Nagumo, et al have revealed that vacancies are stabilized and agglomerated into nano voids in the presence of hydrogen. 17) Therefore, it can be inferred that the heterogeneous concentration of hydrostatic strain in the strain localization region might be attributed to the initiation of some invisible nano voids (<100 nm) due to localized vacancy concentration in the strain localization region.…”
Section: Resultsmentioning
confidence: 99%